THE USE OF K-W-L (KNOW, WANT TO KNOW, LEARN) METHOD IN TEACHING READING HORTATORY EXPOSITION TEXT: A CASE STUDY OF THE ELEVENTH GRADE STUDENT OF MAN 1 BREBES - Tri Rezqi (ETERNAL (English Teaching Journal), 2013)
This research is aimed: 1) to find out how far the improvement of students’ reading comprehension by using K-W-L as teaching method in reading hortatory exposition text, 2) to know students’ responses towards the use of K-W-L method in teaching reading hortatory exposition text. This research used quasi experimental design. The subjects of the study were the eleventh grade students in MAN 1 Brebes in the academic year 2012/2013 as the population. There were only two classes took as sample that collected purposively based on the same number of students. The data were collected through pre-test, post-test and questionnaire.